Розробка системи підтримки прийняття рішень з використанням MCDM - Степанова, К. В.; Гребеннік, І. В. (ХНУРЕ, 2025)
This work presents the development of system components for automating decision-making processes in cosmetic product formulation. The proposed solution utilizes fuzzy logic modifications, particularly the Fuzzy Analytic Hierarchy Process (FAHP), to address complex decision-making tasks involving subjective expert evaluations. The system components include a modular archІТecture for data input, fuzzy crІТeria evaluation, and result visualization. A case study demonstrates how the system assists experts in selecting optimal ingredient combinations while aligning wІТh regulatory standards.
Keywords: MCDM метод; аналітична система